Students' Perceptions of the Challenges of ESP Courses: A Study from an Indonesian University - Suherman, Andri (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
The current study aims to investigate challenges experienced by ESP students. Conducted at the University of Hamzanwadi (East-Lombok, Indonesia), this study employs both quantitative and qualitative methods with two instruments to collect data, questionnaires and interviews. The questionnaire was electronically sent out to 100 ESP students to discover challenges they have been dealing with, which was then statistically analyzed. In addition, semi-structured interviews were carried out with a representative of 20 ESP students to examine their perceptions of the challenges, which were then qualitatively analyzed using a coding system. The results of quantitative data revealed that the students have been experiencing 5 types of challenges in learning ESP with Linguistic Competence and University Support being the two most challenging issues for over 90% of students. Meanwhile, the qualitative data showed that the five challenges were intercorrelated and affected each other. Pedagogical implications gained from this study include university officials should provide support to facilitate ESP students with potential challenges and to help them eradicate the challenges. Despite these, several limitations in this study are found including it recruited a relatively small number of participants, and it missed to explore solutions that students have employed to tackle the challenges as it can provide us with meaningful insight into the general overview of ESP courses from students’ perspectives.